Prevalence of intestinal protozoa in an aborigine community in Pahang, Malaysia - Noor Azian, M.Y.; San, Y.M.; Gan, C.C.; Yusri, M.Y.; Nurulsyamzawaty, Y.; Zuhaizam, A.H.; Maslawaty, M.N.; Norparina, I.; Vythilingam, I. (2007)
The objective was to estimate the prevalence of intestinal protozoa among the aborigines and to determine the problems regarding the infection. The study was carried out in January 2006 in Pos Senderut, Pahang, Malaysia. Samples of faeces were collected from children and adults and these were fixed in PVA and trichrome staining was carried out. From the 130 individuals studied, 94 (72.3) were positive with at least one intestinal protozoa. Nine intestinal protozoa namely Blastocystis hominis, Giardia lamblia, Entamoeba histolytica, Entamoeba coli, Endolimax nana, Entamoeba hartmani, Entamoeba polecki, Iodamoeba butschlii and Chilomastix mesnili were detected. The prevalent species were B. hominis (52.3), followed by G. lamblia (29.2), E. coli (26.2) and E. histolytica (18.5). The other species ranged from 1.5 to 10.8. Among the positive samples, mixed infection with E. histolytica and G. lamblia was 3.8, E. histolytica and B. hominis was 15.4, G. lamblia and B. hominis was 17.7. Triple infection of E. histolytica, G. lamblia and B. hominis was 3.1. The infection was more prevalent in children below 10 years age group (45.4) and lowest in the age above 60 years (3.8). The high prevalence was attributable to poor environmental management, poor personal hygiene and lack of health education.